Extracellular vesicles derived from immortalized human natural killer cell line NK3.3 as a novel therapeutic for multiple myeloma - Matchett, Emily C.; Kornbluth, Jacki (Frontiers in Immunology, 2023)
Over the last decade, there have been many advancements in the therapeutic treatment of multiple myeloma (MM), including the use of natural killer (NK) cells. However, despite promising results from clinical trials, there are concerns over the use of NK cell-based therapy. Cells often undergo growth arrest, limiting their experimental utility; donor cells are extremely heterogeneous, resulting in content variability; and patients receiving allogeneic cells are at risk for graft-versus-host disease and/or cytokine release syndrome. Extracellular vesicles (EVs) have emerged as a new natural therapeutic tool. EVs are known to carry cargo derived from the parent cell from which they originate. NK cells play an important role in the innate immune system, targeting and killing tumor cells. This has led many researchers to isolate EVs from NK cells for their cytotoxic potential. In this study, we isolated EVs from the NK cell line, NK3.3, which was derived from the peripheral blood of a healthy donor. Currently, it is the only normal human NK cell line reported with all the functional characteristics of healthy NK cells. To address the issue of growth arrest, we immortalized NK3.3 cells with lentivirus encoding the catalytic subunit of human telomerase htert (NK3.3-LTV). EVs from these cells were isolated using a modified polyethylene glycol (PEG)-acetate precipitation protocol to simplify processing and increase EV yield. We demonstrated that NK3.3-LTV EVs target both sensitive and drug-resistant MM cell lines as well as primary patient MM cells in vitro, decreasing proliferation and inducing apoptotic cell death as well as or better than EVs from non-immortalized cells with no toxicity towards normal cells. This study is the first step towards developing an immunotherapeutic product designed to treat patients with relapsed/refractory MM.